Women in the Qur'an, Traditions and Interpretation: By Barbara Freyer Stowasser. Oxford, UK: Oxford University Press, 1994, 206 pp. (American Journal of Islam and Society, 1995)
It takes a book like Barbara Freyer Stowasser's Women in theQur'an, Traditions and Interpretation to help extricate the compleximages of Muslim women from the gross overgeneralization characteristicof popular western media. Truly understanding that complexityrequires a look at all of the components that make up the Islamic worldview,from its primary sources ideologically to its cultural history as ithas affected the lives of Muslims. Such a look has been offered inStowasser's book.I was very excited by the cross-referential methodology proposed bythe author in her introduction and her actual use of it throughout the text.She moves among Qur'anic passages, earlier tafasir, hadith traditions, aswell as among contenders in modem Islamic discourse: modernists, traditionalists,and fundamentalists (pp. 5-7). As a result, the reader viewsdifferent responses to ideas about specific women from the Qur'anic textwhile knowing precisely the source of certain ideas.This is not the usual diatribe that confuses indiscriminately fact withmythology, intellectual tradition with popular culture, and results in misinformingthe already ill-informed reader. Moreover, Stowasser avoidsthe other popular extreme: diminishing everything to a single factor, suchas gross misogyny, for example. Although she distinguishes between thevarious strains that make up a complex picture, she does not merelyregurgitate the historical legacy but rather offers critical analysis anddemonstrates her capability in deciphering the various components in theinternal Islamic debates as well.Perhaps the complexity of the cross-referential methodology limits thebreadth of the subject matter. We can understand how complex notions ofthe place of Muslim women in society have resulted from these variousreferences, even though we get no hint at what that place is from this work.The characters analyzed are limited to the specific female characters givenindividual attention in the Qur'anic text and to the wives of the Prophet.These models of virtue and .struggle, failure and frustration, can and have ...